Eye-controlled virtual keyboard using a new coordinate transformation of long and narrow region - Lin, Chern-Sheng; Lin, Chia-Hau; Lay, Yun-Long; Yeh, Mau-Shiun; Chang, Hsing-Cheng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In this paper, we present the development of an eye-tracking and virtual keyboard control system using a PC camera.The image inputs at the channel of the PC camera directly and we can control the cursor of the screen through the sequential image processing. Three-section-correction method is used to correct the eye controlled system. The pupil center position corresponding to the gaze spot on the screen is used to calculate the mouse’s motion coordinate on the screen with new coordinate transform equations for the long and narrow region. With the combination of the new eye-tracking and control algorithms, the sensitivities and operations of these systems would be improved greatly.
Optica Applicata, Vol. 38, 2008, nr 2, s. 481-489
Keywords: optyka; eye-tracking; virtue keyboard; three-section-correction method